Cost and Outcome of Minimally Invasive Techniques for Coronary Surgery Using Robotic Technology. Issue 4 (July 2018) - Pasrija, Chetan; Kon, Zachary N.; Ghoreishi, Mehrdad; Lehr, Eric J.; Gammie, James S.; Griffith, Bartley P.; Bonatti, Johannes; Taylor, Bradley S.
Objective: Totally endoscopic coronary artery bypass (TECAB) with robotic distal anastomosis and robotic-assisted minimally invasive coronary artery bypass (RA-MIDCAB) with robotic internal mammary artery harvest and direct hand-sewn distal anastomosis via an anterior thoracotomy have both been reported as safe and efficacious. We compared hospital cost and short-term outcomes between these techniques. Methods: Patients who underwent robotic-assisted minimally invasive single-vessel Coronary artery bypass grafting (2011–2014) were retrospectively reviewed. One hundred consecutive patients underwent either TECAB (n = 50) or RA-MIDCAB (n = 50). The two groups were sequential with TECAB performed by one surgeon in the first portion of the study interval and RA-MIDCAB by another surgeon in the latter. Demographics, short-term outcomes, and hospital cost data were compared between the two groups. Results: Patient demographics and preoperative risk factors were similar between the TECAB and RA-MIDCAB groups, as total operating room time. Cardiopulmonary bypass was used for 56% of TECAB and 0% of RA-MIDCAB cases ( P < 0.001). Intensive care unit and hospital lengths of stay, along with postoperative morbidities, were similar between the two groups. Operative mortality was 2% in the TECAB and 0% in the RA-MIDCAB group ( P = NS). Total hospital cost was significantly higher with TECAB compared with RA-MIDCAB (US $33, 769 vs. $22, 679, P < 0.001), which was primarily driven by operative costs (US $17, 616 vs. $26, 803, P < 0.001). Conclusions: Totally endoscopic coronary artery bypass and RA-MIDCAB both demonstrated excellent short-term clinical outcomes. However, TECAB was associated with significantly higher hospital costs. Further comparisons, including long-term outcomes, patient satisfaction, and functional status, are needed to evaluate whether this additional cost is justified.